2014
DOI: 10.1136/oemed-2013-101833
|View full text |Cite
|
Sign up to set email alerts
|

Maternal occupational exposure to polycyclic aromatic hydrocarbons and small for gestational age offspring

Abstract: Objectives While some of the highest maternal exposures to polycyclic aromatic hydrocarbons (PAHs) occur in the workplace, there is only one previous study of occupational PAH exposure and adverse pregnancy outcomes. We sought to extend this literature using interview data combined with detailed exposure assessment. Methods Data for 1997–2002 were analysed from mothers of infants without major birth defects in the National Birth Defects Prevention Study, a large population-based case-control study in the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Several studies from the National Birth Defects Prevention Study (NBDPS) have reported an association between occupational exposures to polycyclic aromatic hydrocarbons (PAHs) and adverse birth outcomes, such as birth defects and small for gestational age offspring (Langlois et al, ; Langlois et al, ; Langlois et al, ; Lupo et al, ; O'Brien et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from the National Birth Defects Prevention Study (NBDPS) have reported an association between occupational exposures to polycyclic aromatic hydrocarbons (PAHs) and adverse birth outcomes, such as birth defects and small for gestational age offspring (Langlois et al, ; Langlois et al, ; Langlois et al, ; Lupo et al, ; O'Brien et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…People's exposures to PAHs -complex mixtures containing over 100 compounds-are associated Prenatal PAHs exposures are harmful to the developing brain, high levels of PAH-DNA adducts in cord blood have been associated with neural tube defects, and occupational exposures during pregnancy increase the risk for small for gestational age babies [25][26][27]. In the U.S.…”
Section: Cognition Effects and Brain Structural Changesmentioning
confidence: 99%
“…For example, studies have reported associations between PAHs and gastroschisis (Lupo, Langlois, et al, 2012), small for gestational age (Langlois et al, 2014), and neural tube defects (Ren et al, 2011). There is also biological evidence that PAHs may be teratogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Any discrepancies were resolved in a consensus meeting, which included a third hygienist. The approach used to estimate PAH exposure has been described previously (Rocheleau et al, 2011) and is described in detail in other NBDPS studies (Langlois et al, 2014; Langlois et al, 2013; Langlois et al, 2012; Lupo, Langlois, et al, 2012; Lupo, Symanski, et al., 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation